(untitled) (Polis (Santiago), 2018)
The aim of this paper is to reconstruct the relationship between the national bourgeoisie, represented by the Union Industrial Argentina, and the State, between 1966 and 1969. This is, to understand the plan of action undertaken by the governemental period calkled “Argentinian Revolution” lead by Juan Carlos Onganía. To this end, we examine the guidelines governing the institution in terms of its wages, tariff, fiscal policy, macroeconomics and politics. We analyze the involvement of the organization, during the government of Juan Carlos Ongania, as an integral part of it. We note which proposals they raised each time and what discussions they held with national authorities.